Structure and Properties of Novel Fibril Silicate/Rubber Nanocomposites - Tian, M.; Lu, Y.; Liang, W.; Cheng, L.; Zhang, L.
Palygorskite (AT)mineral was selected as a nano-fiber precursor due to its unique structure characteristics and surface chemical property, to construct a novel nano-fiber/rubber nanocomposites by using a simple and cost-efficient preparation method. Upon shear force during traditional mechanical mixing, the numerous nano-fibers contained in palygorskite micro-powder were released into rubber matrix resulted from weak stacking force between nano-fibers and high shear stress associated with high viscosity of rubber matrix. Meanwhile these nano-fibers were orientated along the shear direction the same as micro-short fiber. In situ modification using silane coupling agent can improve the dispersion of AT and strengthen the interfacial bonding between AT and rubber. The result from dynamic mechanical thermal analysis shows that the incorporation of palygorskite into rubber matrix markedly lowers the loss factor of rubber in glassy transition region and increases storage modulus of rubber. These nanocomposites exhibit stress-strain characteristics that are similar to that of micro-short fiber reinforced rubber, evident anisotropy in mechanical properties, good processing properties, as well as low cost and easily practiced by industry.
Keywords: PALYGORSKITE; NANO-FIBER; NANOCOMPOSITES; RUBBER